Нові дані до вивчення ранніх етапів освоєння території Східноєвропейської рівнини у палеоліті - Степанчук, В.М.; Рижов, С.М.; Матвіїшина, Ж.М.; Кармазиненко, С.П. (Інститут археології НАН України, 2008)
Стаття містить дані, що проливають нове світло на ранні етапи освоєння західного сегменту Східноєвропейської рівнини в середньому та верхньому плейстоцені. Наведено археологічні, геостратиграфічні та палеопедологічні свідчення про присутність давнього населення в басейні Південного Бугу вже починаючи з 11-ї киснево-ізотопної стадії (близько 400 тис. років тому), і про перманентне перебування тут населення між КІС 5е та 3, або у часовий проміжок 127-30 тис. років тому. Proposed paper briefly represents results of archaeological, geostratigraphical, and paleopedological studies on a row of newly discovered Palaeolithic localituies in the south of Cherkassy and north of Kirovograd regions of Ukraine, in area of Velyka Vys’ river, till very recently being a “white spot” on the Palaeolithic map of the country. Localities Andreevka 4, Lypianka 1, Korobchino 7, Maslovo 5, Maslovo 5v, Nechaevo 3, and Byrzulovo IX are under discussion. Stratified character of many of these localities is revealed as lithic artifacts were recovered here in sediments correlated to OIS 3, OIS 4, OIS 5c-a, and OIS 5å. It is important the fact of rather permanent presence of Middle Palaeolithic population in Southern Bug basin in course of Upper Pleistocene. Nor less important is discovery of flint artifacts and fauna in Middle Pleistocene sediments (OIS 11) at Maslovo 5v and, probably, Byrzulovo IX localities. New evidence is of great interest and importance for home studies on Palaeolithic.